Efficacy of Garcinia mangostana L. (mangosteen rind extract) to reduce acne severity (Medical Journal of Indonesia, 2013)
Background: In vitro studies showed that extract of mangosteen rind (EMR) (Garcinia mangostana L.) containing xanthones has antibacterial effect against Propionibacterium acnes and also anti-inflammatory effect. The aim of this study is to determine the efficacy of EMR in reducing acne vulgaris (AV). Methods: A randomized, double-blind, placebo controlled clinical trial was done on 94 subjects (18-30 years) with mild and moderate AV. The treatment group was given 400 mg EMR 3 times daily orally, for 3 weeks and control group was given placebo capsules. As a standard therapy, all subjects were given a topical cream of 0.025% retinoic acid applied on acne lesions during night time. Efficacy was assessed by counting the acne lesion number as well as proportion of subjects with more than 20% decrease in lesion. The decrease of plasma malondialdehyde (MDA) levels were also measured. Results: After 3 weeks of treatment, acne lesion counts was significantly reduced in both groups [from 934 to 584 lesion (37%) in treatment group, p < 0.001 and from 832 to 608 lesion (27%) in control group, p < 0.001]. Comparison between the two groups revealed a non significant difference (p > 0.55). The proportion of subjects whose acne lesion reduced ≥ 20% was 73% (33 of 45 subjects) in treatment group vs 66% (27 of 41 subjects) in control (p > 0.2). The level MDA was reduced from 1.16 to 1.02 nmol/mL in treatment group and from 1.32 become 1.02 nmol/mL in control (p > 0.48). Conclusion: Extract of mangosteen rind given orally for 3 weeks clinically reduced acne severity better than placebo, although statistically was not significant. Antioxidant effect of EMR seem to be unspecific in reducing acne severity. (Med J Indones. 2013;22:167-72. doi: 10.13181/mji.v22i3.586)